Knowledge accumulation and industry evolution the case of pharma-biotech - Mazzucato, Mariana 1968-; Dosi, Giovanni 1953- (Cambridge University Press, 2006)
Written by internationally acclaimed experts in the economics of innovation, this volume examines how the biotechnology and pharmaceutical sector is affected by the dynamics of innovation, institutions, and public policy. It contributes both theoretically and empirically to the increasingly influential Schumpetarian framework in industrial economics, which places innovation at the centre of the analysis of competition. Both quantitative and qualitative studies are included, and this varied perspective adds to the richness of the volume's insights. The contributors explore different ideas regarding the historical evolution of technology in the sector, and how firms and industry structure have co-evolved with innovation dynamics. Important policy questions are considered regarding the future of innovation in this sector and its impact on the economy
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Pharmaceutical biotechnology; Research, Industrial; Industrial organization (Economic theory); Technological innovations; Pharmazeutische Industrie; Biotechnologische Industrie; Produktinnovation; Unternehmenswachstum